Dragons of fate - Weis, Margaret; Hickman, Tracy (Weis, Margaret. Dragonlance destinies, 2023)
"A courageous heroine trapped in the distant past is determined to return to her own time-without changing the shape of the world forever-Dragonlance series continues in this sequel to Dragons of Deceit"--